The influence of expectations on shame, rumination and cognitive flexibility: an experimental investigation on affect-regulatory characteristics of deceptive placebos - Schäfer, Leonora Nina; Rief, Winfried (Frontiers in Psychology, 2025)
BackgroundSeveral studies identified affect-regulatory qualities of deceptive placebos within negative and positive affect. However, which specific characteristics of an affect-regulatory framing impacts the placebo effect has not yet been subject to empirical investigations. In particular, it is unclear whether placebo- induced expectations of direct emotion inhibition or emotion regulation after emotion induction elicit stronger effects in affect regulation.PurposeThe aim of the study was to identify whether specifically framed expectations on the occurrence (antecedent-focused) vs. regulation capability (response-modulating) of affect, induced with an active placebo nasal-spray, have effects on affect-regulatory processes. Because personality traits have been suspected to influence placebo responses and affect regulation, an additional goal of the study was to examine modulating influences of shame proneness, level of depression, experiential avoidance, and emotional control.MethodsHealthy volunteers (n = 121) were randomized to either a deceptive placebo condition (antecedent-focused vs. response-modulating instruction) or a no-treatment control group before shame was experimentally induced via autobiographical recall. Groups were compared on outcomes of state shame, rumination, and cognitive flexibility.ResultsBoth antecedent-focused and response-modulating placebo framings influenced changes in state shame (b = 3.08, 95% CI = [0.80–5.92], p = 0.044), rumination (b = 4.80, 95% CI = [1.50–8.09], p ≤ 0.001) and cognitive flexibility outcomes (b = −3.63, 95% CI = [−6.75 – −0.51], p = 0.011) after shame-induction interventions. Only the antecedent-focused placebo response was modulated by personality traits. Experiential avoidance modulated shame experience (F(2,115) = 3.470, p = 0.031) whereas emotional control influenced the reports of state rumination (F(2,115) = 4.588, p = 0.012). No modulatory influences of levels of depression and shame proneness could be observed (ps > 0.05).ConclusionThe results suggest that shame, rumination and cognitive flexibility can be positively influenced by placebo treatment in healthy subjects. Personality traits of emotional control and experiential avoidance influenced the placebo response of the antecedent-focused treatment rationale on outcomes individually.Clinical trial registrationClinicalTrials.gov, identifier NCT05372744.